Variation in plasma cytokine concentration during a training season in elite kayakers - Borges, G. F.; Rama, L.; Carvalho, H. M.; Gaspar, J.; Santos, A.; Massart, A.; Gomes, B.; Minuzzi, L. G.; Paiva, A.; Teixeira, A. M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this study was to investigate the differences in cytokines levels in the peripheral blood of kayakers at different moments of training. METHODS: The sample comprised 12 elite kayakers preparing for the Beijing Olympic Games. Blood samples were collected at different time points of the training season: baseline (t0-November) after 6 weeks of off-training and before the start of the training season; t1 (January) at week 11 after a period of high-volume training; t2 (April) at week 26 at the end of a period of high intensity training sessions; t3 (June) at week 31 after a competitive period. RESULTS: Decreases in cytokine levels were found for IL-1ß and IL-18 at t1. IL-1 then increased throughout the remaining training season while IL-18 leveled off towards the end of the season. IL-1ra showed an exponential increase at t2 before leveling-off in the last period of training. No significant changes were found for IL-6, IFN-? and TNF-a. No differences were observed in the magnitude and pattern of cytokines changes across the training season between the elite female and male kayakers. CONCLUSIONS: Increases in training volume were able to induce decreases in pro-inflammatory plasma cytokine coinciding with the reported increase in upper respiratory tract infections in the kayakers.